2020
DOI: 10.1007/s40544-019-0342-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the tribological performance of ionic liquids in non-conformal EHL contacts under electric field activation

Abstract: Real-time external alteration of the internal properties of lubricants is highly desirable in all mechanical systems. However, fabricating a suitable and effective smart lubricant is a long-lasting experimental process. In this study, the film thickness and frictional response of ionic liquid-lubricated non-conformal contacts to an electric field excitation under elastohydrodynamic conditions were examined. Film thickness was evaluated using a "ball-on-disc" optical tribometer with an electric circuit. Frictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…ILs have high electrical responsiveness. [ 46 ] Through our experiment on the electric control of friction, it was found that the base lubricating oil could respond quickly to the electric stimulation with only a small amount of IL. According to the friction and wear experiment, the surface wear of the friction pair was almost zero when the load was 2.5 N. To minimize the influence of the change of the interface contact forms of the friction pairs on the experimental results, the electrically controlled friction experiment was first carried out in the reciprocating module under the load of 2.5 N at 25 °C, and the other parameters were consistent with the setting of the friction and wear experiment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ILs have high electrical responsiveness. [ 46 ] Through our experiment on the electric control of friction, it was found that the base lubricating oil could respond quickly to the electric stimulation with only a small amount of IL. According to the friction and wear experiment, the surface wear of the friction pair was almost zero when the load was 2.5 N. To minimize the influence of the change of the interface contact forms of the friction pairs on the experimental results, the electrically controlled friction experiment was first carried out in the reciprocating module under the load of 2.5 N at 25 °C, and the other parameters were consistent with the setting of the friction and wear experiment.…”
Section: Resultsmentioning
confidence: 99%
“…This caused an instant increase in viscosity, and the sliding movement required overcoming sticky resistance, showing an increase in the coefficients of friction. [ 46 ] As the circuit current increased, the attraction between the tribo‐pairs increased and more ions moved to the lubrication layer, which further increased the viscosity resistance, resulting in a larger coefficient of friction. In contrast, the lubricant had a liquid‐like structure with significantly weaker intermolecular binding force when little or no current was applied, resulting in a smaller coefficient of friction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical computational fluid dynamics and theoretical approaches to describe the mechanisms of oil injection in case of lubrication of high-speed spur gears were presented by Wang et al (2018). Finally, producing smart lubricants is also an up-to-date approach that can be used for high-speed assemblies (Michalec et al , 2020).…”
Section: Introductionmentioning
confidence: 99%